CONTINUOUS AND COMPREHENSIVE EVALUATION - DWIVEDI, ARTI (THE PRIMARY TEACHER, 2013)
We all are aware about the Right of Children to Free and Compulsory Education Act, 2009 (RTE Act, 2009), implemented since April 2010. It says, “Every child of the age group of 6-14 years shall have a right to free and compulsory education in a neighbourhood school till completion of elementary education.” With the implementation of Act, every child has the right to get quality education. The Act demands that CCE should be implemented for each child till the completion of elementary schooling. The field experiences and interactions with teachers suggested that teachers are facing problems in implementation of CCE. Teachers are largely engaged in compiling the data and keeping the records of children’s test results rather than implementing CCE during the teaching-learning process. CCE is generally considered by them as an external activity to be conducted after the teaching. Most of the teachers are not confident about implementing CCE